Teaching ESP during emergency remote learning (ERL): Best practices - Mandasari, Yuyun Putri; Wulandari, Eka (ELT Forum: Journal of English Language Teaching, 2021)
After a year more of living with COVID-19, the teachers’ and students’ resilience is still demanding, particularly regarding language online learning. Both parties must keep struggling to fulfill the learning requirements in times of crisis. One of the challenges in language issues is teaching English for Specific Purpose (ESP) in higher education during emergency remote learning (ERL) including teaching ESP at Poltekkes Kemenkes Malang in 2020-2021. At these times, ESP teachers have to design the materials by taking a lot of consideration regarding the students’ needs, goals, learning model, activities, tools, and feedback that met the emergency due to Coronavirus outbreak. They planned, implemented, and evaluated the learning process until they can find the best ones for the students. This study was a survey research with 23 participants of ESP lecturers. This article presented some best practices of teaching ESP in the online mode during ERL as the best experience of ESP lecturers, in the hope that it will be able to give some new insights for fellow educators to help them to provide better learning experiences for the students.